2010
DOI: 10.1016/j.cell.2010.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Nfix Regulates Fetal-Specific Transcription in Developing Skeletal Muscle

Abstract: Skeletal myogenesis, like hematopoiesis, occurs in successive developmental stages that involve different cell populations and expression of different genes. We show here that the transcription factor nuclear factor one X (Nfix), whose expression is activated by Pax7 in fetal muscle, in turn activates the transcription of fetal specific genes such as MCK and beta-enolase while repressing embryonic genes such as slow myosin. In the case of the MCK promoter, Nfix forms a complex with PKC theta that binds, phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
239
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 189 publications
(248 citation statements)
references
References 41 publications
9
239
0
Order By: Relevance
“…NFI transcription factors can activate and repress gene transcription depending on the gene and cellular context (Chang et al, 2013;Gronostajski, 2000;Messina et al, 2010). NFIB influences stem cell maintenance and differentiation in several tissues including in the SVZ as part of a cross-regulatory network together with Pax6/Brg1 (Chang et al, 2013;Ninkovic et al, 2013 (Chang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…NFI transcription factors can activate and repress gene transcription depending on the gene and cellular context (Chang et al, 2013;Gronostajski, 2000;Messina et al, 2010). NFIB influences stem cell maintenance and differentiation in several tissues including in the SVZ as part of a cross-regulatory network together with Pax6/Brg1 (Chang et al, 2013;Ninkovic et al, 2013 (Chang et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…6A; Supplemental Fig. S5A-D; Messina et al 2010). EdU incorporation and flow cytometry analysis showed that in proliferation conditions, Nfix shRNA-expressing and control cells proliferated at the same rate, suggesting that Nfix does not play a major role in NS cell proliferation (Supplemental Fig.…”
Section: Nfix Is Both Required and Sufficient To Induce Aspects Of Qumentioning
confidence: 99%
“…shRNA knockdown of Nfix Lentiviral particles encoding a control or Nfix-specific shRNA construct and a puromycin resistance cassette (Messina et al 2010) were generated in 293T cells according to standard procedures. Proliferating NS cells were transduced with the lentiviruses, and, 24 h later, 2 mg/mL puromycin was added to select for shRNA-expressing cells.…”
Section: Ns Cellsmentioning
confidence: 99%
“…TGF-b family members inhibit muscle differentiation and growth following receptor binding and the initiation of specific intracellular signals by Smad2 and Smad3 proteins, whereas BMP signaling through Smad1, Smad5 and Smad8 is a positive regulator of muscle growth (Gardner et al, 2011;Sartori et al, 2009;Sartori et al, 2013;Winbanks et al, 2013). Recent data have also implicated specific members of the nuclear factor I (NFI/Nfi) family of transcription factors in muscle morphogenesis (Gronostajski, 2000), Nfia being responsible for the induction of embryonic muscle genes, whereas Nfix activates fetal genes (Messina et al, 2010).…”
Section: Introductionmentioning
confidence: 99%